The rural development challenge in OECD member countries - Huillet C. (Strengthening endogenous development patterns in European agriculture, 1993)
The author stresses the need for well-defined rural policies. He argues a two-tiered approach is required. On the one hand general measures are necessary that take into account the circumstances of each rural setting. The importance of the institutional dimension is underlined.
Seminar on 'Strengthening Endogenous Development Patterns in European Agriculture', 1992/10/20-22, Chania (Greece)